Implementasi Metode Agile pada Sistem Manajemen Zakat Berbasis Website dengan Framework Laravel - Hakam, Muhammad Aulia; Triayudi, Agung; Hayati, Nur (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2022)
The implementation of paying zakat is obligatory for every Muslim. Generally, there are problems that are lacking in the recording of zakat management. Currently, many still use the manual method which is of course very risky for loss and damage to the recording of zakat. Therefore, the purpose of this study is to design a website that facilitates the payment and recording of zakat. With this research, it is expected to ease the mosque management to manage zakat to be more efficient. In this study applying the Agile SDLC model, this study has four stages, namely, timebox planning, iteration, demonstration, and retrospective meeting. Based on the research that has been done, namely the Implementation of Agile Methods on a Website-Based Zakat Management System with the Laravel Framework at the Al-Ijabah Mosque Amil Zakat Agency, the researcher concludes that the system built has met the administrative needs to input data such as Muzakki data (zakat givers). , Mustahiq data (zakat recipients), daily transaction reports. With the construction of this system, zakat transaction data can be stored in the database. So that zakat transaction data is not easily lost/damaged.